Playing the Whack-A-Mole Game: ERK5 Activation Emerges Among the Resistance Mechanisms to RAF-MEK1/2-ERK1/2- Targeted Therapy - Tubita, Alessandro; Tusa, Ignazia; Rovida, Elisabetta (Frontiers in Cell and Developmental Biology, 2021)
Molecularly-tailored therapies have opened a new era, chronic myeloid leukaemia being the ideal example, in the treatment of cancer. However, available therapeutic options are still unsatisfactory in many types of cancer, and often fail due to the occurrence of resistance mechanisms. With regard to small-molecule compounds targeting the components of the Mitogen-Activated Protein Kinase cascade RAF-MEK1/2-ERK1/2, these drugs may result ineffective as a consequence of the activation of compensatory pro-survival/proliferative signals, including receptor tyrosine kinases, PI3K, as well as other components of the Mitogen-Activated Protein Kinase family such as TPL2/COT. The Mitogen-Activated Protein Kinase ERK5 has been identified as a key signalling molecule in the biology of several types of cancer. In this review, we report pieces of evidence regarding the activation of the MEK5-ERK5 pathway as a resistance mechanism to RAF-MEK1/2-ERK1/2 inhibitors. We also highlight the known and possible mechanisms underlying the cross-talks between the ERK1/2 and the ERK5 pathways, the characterization of which is of great importance to maximize, in the future, the impact of RAF-MEK1/2-ERK1/2 targeting. Finally, we emphasize the need of developing additional therapeutically relevant MEK5-ERK5 inhibitors to be used for combined treatments, thus preventing the onset of resistance to cancer therapies relying on RAF-MEK1/2-ERK1/2 inhibitors.